Criminal Liability in Cases of Homosexual Conduct Involving Members of the Indonesian National Armed Forces: A Legal and Human Rights Perspective - Limaria Johana Hutagalung; Mompang L.Panggabean; Hendri Jayadi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The issue of homosexuality within the Indonesian National Armed Forces (TNI) raises complex legal problems as it lies at the intersection of national criminal law, military criminal law, military discipline, and human rights protection. Under Indonesian national criminal law, homosexuality as a sexual orientation is not explicitly criminalized. However, in military legal practice, homosexual conduct may be considered a violation of morality, military discipline, and institutional honor. This situation creates legal issues concerning the basis of criminal liability, legal certainty, and the conformity of law enforcement with the principles of the rule of law and human rights protection. The problems examined in this study are how criminal liability is imposed on members of the Indonesian National Armed Forces who engage in homosexual conduct based on Decision Number 24-K/PM.III-12/AD/II/2020, and how Indonesian criminal law reform should address homosexual conduct within the military environment. This research employs normative legal research using statutory, case, and conceptual approaches. The study utilizes primary, secondary, and tertiary legal materials, which are analyzed qualitatively. The results of the study indicate that criminal liability imposed on TNI members in Decision Number 24-K/PM.III-12/AD/II/2020 is fundamentally based on the military legal framework that emphasizes discipline, military ethics, and institutional honor as legal interests requiring protection. However, from the perspective of criminal law and human rights, such application still raises issues concerning the principle of legality and legal certainty, as there is no explicit regulation governing homosexuality within the military environment. Furthermore, national criminal law reform through Law Number 1 of 2023 concerning the Criminal Code has not specifically provided comprehensive regulation for military legal subjects in this context. The conclusion of this study is that a more comprehensive criminal law reform is necessary through harmonization between national criminal law, military criminal law, military disciplinary law, and internal regulations of the Indonesian National Armed Forces, in order to create legal certainty, consistency in law enforcement, and a balance between military institutional interests and human rights protection.